Gullibility's Travels - Blumenfeld, Warren S.; Leveto, Gregory A. (Academy of Management Journal, 1975)
The article discusses test validation as an area of concern for professional industrial psychologists. Rather than being viewed as a practical necessity, the conduct of test validation work has been considered an academic requirement. The three main reasons for conducting test validation research are noted as being managerial, scientific and legal. Regardless of the selection technique being utilized, organizations must show that the technique is job related. The author looks at a personality inventory study among personnel managers, noting the affects of gullability on the outcome.